The land reallocation model in the course of agricultural land consolidation in Ukraine - Bugaіenko Olena (Geodesy and Cartography, 2018)
The issue of the effectiveness of agricultural land consolidation in the environment of land relations being reshaped, with Ukraine as the example has been scrutinized in the research. Land reallocation as the key constituent of land consolidation has been considered according to the existing approaches. Necessity for substantiation of the peerness of land plots to be reallocated has been singled out. Key factors influencing the peer agricultural land exchange in the process of reallocation have been defined. It is offered to define the peerness of agricultural land plots by a set of qualitative and spatial and technological characteristics. The improvement of the existing approaches to land reallocation by limiting for the reallocated land plots peerness by the preset characteristics has been suggested. The gist of the modelling is the minimization of distance from land plot to the farmhouse. Technical data characterizing the qualitative and spatial and technological characteristics of land plots at the reallotment have been defined. The assessment of the provided reallocation model with the example of the agricultural land mass has been provided. Land reallocation is accomplished by the voluntary land plot exchange. The analysis of the reallocation results using the provided model has been executed.